U.S. Antidumping : Much Ado About Zeroing - Bown, Chad P.; Prusa, Thomas J. (2012)
The United States use of "zeroing" in its antidumping procedures has become a political flash point threatening some legitimacy of the WTO's dispute settlement system. This paper provides a positive analysis of the zeroing issue, explains how it has evolved and who is likely to be affected by it. The authors use economic theory to identify how export price volatility accentuates the impact of zeroing on the size of U.S. antidumping tariffs and review the WTO caseload over zeroing. They describe the impact that the U.S.'s retrospective system for assessing antidumping margins has on zeroing and the political economy implications as the U.S. struggles to generate policy reform. The authors survey existing evidence of the impact of the zeroing on dumping margins and contribute their own evidence to suggest that zeroing is just as likely to impact the size of U.S. antidumping duties applied on developing country exports as developed economy exports. Thus while developed economies have filed the vast majority of WTO disputes against the U.S. over zeroing, the authors conclude that zeroing is also likely a relevant issue for developing country exporters as over 60 percent of the product lines currently subject to U.S. antidumping are exported by developing countries.